Do data policy restrictions impact the productivity performance of firms and industries?. Issue 3 (7th February 2020) - Ferracane, Martina Francesca; Kren, Janez; van der Marel, Erik
Abstract: This paper examines how policies regulating the cross‐border movement and domestic use of electronic data on the internet impact the productivity of firms in sectors relying on electronic data. In doing so, we collect regulatory information on a group of developed economies and create an index that measures the regulatory restrictiveness of each country's data policies. The index is based on observable policy measures that explicitly inhibit the cross‐border movement and domestic use of data. Using cross‐country firm‐level and industry‐level data, we analyse econometrically the extent to which these data regulations over time impact the productivity performance of downstream firms and industries, respectively. We show that stricter data policies have a negative and significant impact on the performance of downstream firms in sectors reliant on electronic data. This adverse effect is stronger for countries with strong technology networks, for servicified firms, and holds for several robustness checks.